Investigation of the Usefulness of Methyl Ergonovine Application in Cesarean Section Cases - Kumru, Selahattin; Gurates, Bilgin; Parmaksiz, Cem (Galenos Yayincilik, 2005)
Objective: In caesarean sectioned patients after the removal of the fetus, cases treated by oxytocin only and oxytocine combined with methyl ergonovine were compared for their bleeding volume during and until three days after surgery. The difference in the incidence of endometritis between two groups were also determined. Materials and Methods: Caesarean sectioned 55 patients who applied for medical care to the Firat University School of Medicine, Department of Obstetrics and Gynecology Division of Obstetrics between August 2003 and March 2004 were randomised into two groups. After the removal of the fetus, one group (Group 1, n=35) received oxytocine only infusion and the other group (Group 2, n=20) received methyl ergonovine along with oxytocine treatment. Volume of bleeding and lochia during and until three days after surgery along with the development of endometritis in two groups were compared. Independent samples t test and chi-square test were used to determine the significance of the differences between groups. Results: The bleeding volume during the operation was lower in the group receiving oxytocin plus methyl ergonovine than the group receiving oxytocin only (p<0.05, independent samples t test). The amount of bleeding and lochia between two groups until the third day of the surgery were similar (p>0.05, independent samples t test). Endometritis was not observed in any of the patients. Conclusion: In caesarean sectioned patients after the removal of the fetus, oxytocine with methyl ergonovine infusion may decrease the volume of bleeding during the operation. We have not determined any obvious benefit in continuing oxytocin plus methyl ergonovine infusion after the surgical procedure.
Sezaryen olgularinda metil ergonovin uygulamasinin yararlili?inin araştirilmasi
Keywords: caesarean section; oxytocin; methyl ergonovine; bleeding; endometritis